1978
DOI: 10.1073/pnas.75.1.356
|View full text |Cite
|
Sign up to set email alerts
|

Role of contact inhibition in the regulation of receptor-mediated uptake of low density lipoprotein in cultured vascular endothelial cells.

Abstract: Bovine vascular endothelial cells during logarithmic growth bind, internalize, and degrade low density lipoprotein (LDL) via a receptor-mediated pathway. However, contact-inhibited (confluent) monolayers bind but do not internalize LDL. This is in contrast to aortic smooth muscle cells or endothelial cells that have lost the property of contact inhibition. These cells internalize and degrade LDL at both high and low cell densities. The LDL receptors of smooth muscle and sparse endothelial cells down-regulate i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
64
2

Year Published

1980
1980
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 150 publications
(74 citation statements)
references
References 23 publications
8
64
2
Order By: Relevance
“…This is in contrast with the cessation of LDL internalization observed in 221 established lines of bovine endothelial cells upon development of contact inhibition [11] and cannot be attributed to the lack of fibroblast growth factor in the culture medium, since Coetzee et al have reported similar results for human endothelial cells cultured in the presence of fibroblast growth factor [12]. Because our cultures were exposed to lipoprotein-deficient serum prior to testing, and may thus have increased their number of LDL receptors [3], our results may overestimate the magnitude of LDL receptor activity expressed by endothelial cells in vivo.…”
Section: Discussioncontrasting
confidence: 73%
See 4 more Smart Citations
“…This is in contrast with the cessation of LDL internalization observed in 221 established lines of bovine endothelial cells upon development of contact inhibition [11] and cannot be attributed to the lack of fibroblast growth factor in the culture medium, since Coetzee et al have reported similar results for human endothelial cells cultured in the presence of fibroblast growth factor [12]. Because our cultures were exposed to lipoprotein-deficient serum prior to testing, and may thus have increased their number of LDL receptors [3], our results may overestimate the magnitude of LDL receptor activity expressed by endothelial cells in vivo.…”
Section: Discussioncontrasting
confidence: 73%
“…The inverse relationship between degree of confluency and rate of LDL degradation described in bovine aortic endothelium [11] was also demonstrated in human endothelial cells (Fig.l) (Fig. 1).…”
Section: Effects Of Elevated Glucose On Uptake and Degradation Of Natsupporting
confidence: 57%
See 3 more Smart Citations